STUDI PIROLISIS MIKROALGA HIJAU (Spirulina platensis) TERHADAP KONSENTRASI PRODUK TURUNAN KLOROFIL - Mardiani, Evi; Subagyono, RR Dirgarini Julia Nurlianti; Allo, Veliyana Londong (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Pyrolysis study of green microalgae (Spirulina platensis) using Pyrolysis-Gas Chromatography-Mass Spectrometry (Py-GC/MS) instrument has been conducted. In this study, the Spirulina platensis microalgae used had a moisture content of 8.34% and an ash content of 7.18%. Pyrolysis of Spirulina platensis microalgae at 450˚C produced chlorophyll derivative products of 6.20%. Keywords : Spirulina platensis, pyrolysis, Py/GC-MS